Continuing Professional Development at Two Rural Hospitals in Ecuador - David Gaus; James Conway; Diego Herrera (Ubiquity Press, 2024)
Background: E-learning Continuing Professional Development (CPD) is an activity demonstrated to improve the quality of healthcare delivery. The CPD of medical and nursing staff in high income countries (HICs) is commonplace. CPD of administrative staff is less common, but increasingly frequent. In low- and middle-income countries (LMICs), CPD of any kind is infrequent, particularly in rural and remote areas. Objective: The aim of this study was to describe a hospital-based e-learning CPD program for clinical and non-clinical personnel as a unique example of a successful, ongoing educational pilot, quality improvement program involving a broad cohort of employees, in a country that does not require such activities. Methods: Using the online educational platform Chamilo, e-learning modules were created for eight groups including clinical and non-clinical employees. Upon completion of each module, one to two paragraph discussions were provided for each incorrect answer submitted. Two additional chances were offered for the employee to achieve a passing score of 70%. This study reports on the first 10-month period of the program. Findings: All participants achieved the 70% passing threshold after the first or second attempt. There was 100% participation by the employees required to complete the e-learning modules. Employee feedback suggested the modules were good for continuing education, but some felt the CPD was imposed on them. Conclusion: E-learning CPD is an important and emerging element for CPD and may provide opportunities for healthcare service quality improvement as part of broader pedagogical modalities, such as conferences and directed readings, in rural and remote areas of LMICs. These pilot programs could provide important information to develop Spanish-language e-learning CPD programs across a broader region, promote collaboration with regional professional societies, and possibly contribute to the establishment of national health program CPD standards.